Smartphone dependence, addiction, and insomnia among medical students during the COVID-19 pandemic - Virgilio E. Failoc-Rojas; Alicia Torres-Mera; Darwin A. León-Figueroa; David Lira; Flor M. Santander-Hernández; Miguel A. Guevara-Morales; Cristian Díaz-Vélez; Mario J. Valladares-Garrido (PLoS ONE, 2025)
Introduction During the COVID-19 pandemic, smartphone use among students increased, even before going to sleep, which resulted in an increased risk of dependence, addiction, and sleep problems such as insomnia and daytime somnolence. The objective of this study was to determine the association between different levels of problematic smartphone use (dependence and addiction) and insomnia among medical students. In this study, “dependence” refers to subclinical, yet compulsive, smartphone use, while “addiction” denotes a more severe behavioral disruption involving loss of control and functional impairment. Materials and methods This was a secondary cross-sectional study of a cohort of medical students from Piura (Peru) during the COVID-19 pandemic in 2020. The study included 370 participants. Insomnia was assessed using the Insomnia Severity Index, and the extent of smartphone use was determined using the Smartphone Dependence and Addiction Scale. A chi-squared test was used for the bivariate analysis, and prevalence ratios (PR) were estimated using Poisson regression with crude and adjusted models and 95% confidence intervals (CI). Results Insomnia was reported by 67.8% of participants. Smartphone dependence was identified in 67.8% of students, and 10.8% met the criteria for addiction. The prevalence of insomnia was notably higher among students aged ≥26 years (80.0%) and among those with symptoms of depression (79.3%) and anxiety (81.9%). After adjusting for potential confounders, students classified as dependent were 1.43 times more likely to report insomnia (aPR: 1.43; 95% CI: 1.10–1.86), while those classified as addicted showed an even higher association (aPR: 1.66; 95% CI: 1.26–2.17), compared to nondependent users. Conclusion Both smartphone dependence and addiction were significantly associated with a higher prevalence of insomnia among medical students. These findings highlight the need for preventive strategies targeting problematic smartphone use to promote better sleep health in academic settings.